1981
DOI: 10.5006/1.3580800
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Determination of Potential Distributions and Current Densities in Multi-Electrode Systems

Abstract: Two numerical solution methods of the Laplacian equations, within boundary conditions set by the geometries and electrode reactions of arbitrary cells, are presented. One method is based on the location of current sources on suitable locations in and around the cell. The strength of these sources is a variable. With the solution of the equations of the potential gradients at the boundaries, the strength of the sources is determined, and herewith potentials and current densities. In the second method, the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Most of the previous studies have also reported agreement between modeling predictions and experimental measurements for the galvanic current distribution. [45][46][47][48][49][50][51][52] In contrast, Ault and Meany [53] concluded: a) "the deepest pit was not immediately adjacent to the cathodic metals that most mathematical models predict"; b) "the mathematical model only can provide a order of magnitude estimation of galvanic current flow"; and c) "the mathematical model can neither accurately predict long term current distribution nor the magnitude of pitting corrosion". These conclusions are of particular significance for the present study on the galvanic corrosion of magnesium because localized corrosion is often the form of corrosion of magnesium in practical solutions as typified by 5 % NaCl solution.…”
mentioning
confidence: 99%
“…Most of the previous studies have also reported agreement between modeling predictions and experimental measurements for the galvanic current distribution. [45][46][47][48][49][50][51][52] In contrast, Ault and Meany [53] concluded: a) "the deepest pit was not immediately adjacent to the cathodic metals that most mathematical models predict"; b) "the mathematical model only can provide a order of magnitude estimation of galvanic current flow"; and c) "the mathematical model can neither accurately predict long term current distribution nor the magnitude of pitting corrosion". These conclusions are of particular significance for the present study on the galvanic corrosion of magnesium because localized corrosion is often the form of corrosion of magnesium in practical solutions as typified by 5 % NaCl solution.…”
mentioning
confidence: 99%
“…Let n be the Newton-Raphson solution at the nth iteration with 0 60 and * be the exact solution of (5)- (8). If…”
Section: Discussionmentioning
confidence: 99%
“…Let { n } be the Newton-Raphson iterative sequence and * be the exact solution of (5)- (8). If condition (19) is satisÿed, then the Newton-Raphson iteration converges to the exact solution for arbitrary initial value 0 ¡0 and * ¿ · · · ¿ n ¿ n−1 ¿ · · · ¿ 1 (34)…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Several researchers have studied the internal corrosion problems of oil pipelines [1,2]. In recent times, more researchers have studied the more recently discovered causes and prevention of corrosion in pipelines [3,4].The study of corrosion enables the user of materials to optimize the service life of such materials.…”
Section: Introductionmentioning
confidence: 99%